Organising Organised Sound: A coming of age. - Simoni, Mary (Organised Sound, 2015)
This article puts forth the author’s views on a panorama of contemporary influences that presage the future of higher education. The author describes how these views have shaped a new curriculum and pedagogy at Rensselaer Polytechnic Institute.